On the normative content of Article 18 § 1–3 Criminal Code (Ius Novum, 2021)
The  paper  addresses  the  issue  of  normative  character  of  the  provisions  of Article  18  §  1–3  of  the Penal Code. An attempt has been made - from the standpoint of the determinants of the derivational concept of interpretation of the law and the theory of legislation and rules of legislative technique  –  to  resolve  a  dispute  existing  in  the  science  of  criminal  law  concerning  whether,  in  respect of directing the commission of an offence and solicitation of the commission of an offence the  provisions  of Article  18  §  1  of  the  Penal  Code  are  provisions  supplementing  the  provision  typifying the detailed part of the Penal Code, or whether they express a norm which prohibits directing the commission of an offence or solicitation of the commission of an offence. The first variant of interpretation has been favoured. It was also assumed in the paper that the provisions of Article  18  §  2  and  3  of  the  Penal  Code  are  not  peripheral  regulations,  but  modifiers  of  the  regulations defining the generic type of a prohibited act. Consequently, incitement and aiding and abetting are not separate types of commission of a prohibited act characterised by their own set of statutory traits and they do not supplement the generic description of the type of prohibited act with an additional functional trait. Thus, in any form of criminal complicity, the subjective traits of a generic type of a prohibited act may be identified, including the traits of an executive action.
Keywords: sanctioned norm; forms of accessorial liability; trait of an executive action; peripheral regulation; modifying regulation